Ziziphus ridleyana, a new name for Ziziphus macrophylla Ridl. (Rhamnaceae) - Rasingam, Ladan; Karthigeyan, K. (Phytotaxa, 2020)
The genus Ziziphus Miller (1754: 1547) is one of the economically important genera in the family Rhamnaceae distributed in the tropical and subtropical regions (Mabberley 2008). About 135 species are reported from the world, and most of the species are confined to Asia and America. A few of them extend to the Pacific Islands and Australia (Bhandari & Bhansali 2000; Ara et al. 2008). The genus is characterized by its 3 or 5-nerved leaves, often with stipular spines and drupaceous fruits with a solitary pyrene (Ara et al. 2008). Ziziphus macrophylla Ridley (1931: 494) was described by H.N. Ridley based on the collections by Haviland from Lundo area of Sarawak region, Borneo. He named the species as Z. macrophylla based its long leaves. Unfortunately, it is a later homonym of Ziziphus macrophylla Schimper (1874: 224), a fossil species described based on the leaf from Köflach, Styria, Austria. According to the article 53.1 (Turland et al. 2018), Z. macrophylla Ridley is illegitimate, and hence a new name is proposed here.